Biochemical composition of two giant pill-millipedes of the Western Ghats of India - Ambarish, Cheviri N.; Sridhar, Kandikere R. (Biological Letters, 2016)
Many invertebrates have an unexpected nutraceutical potential and are of nutritional or ethnomedicinal significance to many tribals throughout the world. The giant pill-millipedes of the genus Arthrosphaera are traditionally used as natural medicines by tribals in the Western Ghats of India. In this study, two species of pill-millipedes (Arthrosphaera fumosa and A. magna) were subjected to proximate and biochemical analysis to ascertain their nutritional potential. Bodies of A. fumosa and A. magna (after removal of their intestines) had a low protein content (8-15%) and high quantity of carbohydrates (40-41%). They were rich in many essential elements, especially in calcium. The essential amino acids of pillmillipedes were in high quantities. The level of glycine was the highest, followed by lysine and serine. The fatty acid methyl esters (FAMEs) of males and females consist of high quantities of unsaturated fatty acids. The mono-unsaturated fatty acids were more abundant than poly-unsaturated fatty acids. Palmitic and oleic acids were dominant saturated and unsaturated fatty acids, respectively. The study has revealed for the first time that pill-millipedes of the Western Ghats of India constitute a good source of essential minerals, essential fatty acids, and essential amino acids. Being valuable contributors of organic manure by processing recalcitrant plant lignocellulosic wastes, pill-millipedes become part and parcel of organic farming as well as future nutraceutical sources.